WING PLANFORM INFLUENCE ON FLIGHT CHARACTERISTIC OF ROCKET-LAUNCHED UNMANNED AIR-VEHICLE - Larasmoyo Nugroho (Pusbindiklat - LIPI, 2011)
Design of the wing planform depended on some geometry key factors such as aspect ratio, sweep angle, taper ratio, and angle of incidence. The search for optimum fl ight characteristic could be observed from aerody-namic coeffi cients, fl ight stability, fl ight dynamic, fl ight performance, and fl ight quality. To examine the design of the wing planform, this paper presented an experiment that modify few factors of wing geometry and simulated it concerning the launching phase of the unmanned air-vehicle or UAV using rocket as booster. The optimal design of the wing is a prerequisite for the UAV to achieve its main mission as a national defense missile. Using X-Plane v 8.6 as a fl ight simulation tool, the experimental results showed that a hybrid wing could produce an intermediate grade fl ight characteristic between rectangular wing and delta wing. Rectangular wing tended to produce a highly pitch-up trajectory when catapulted by a rocket booster, while delta wing produced a more stable pitch attitude and more better fl ight performance. This experiment showed that hybrid wing was the appropriate choice for subsonic jet UAV that had to be launched by rocket.